1992
DOI: 10.1126/science.1313189
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Activates the Sphingomyelin Signal Transduction Pathway in a Cell-Free System

Abstract: The mechanism of tumor necrosis factor (TNF)-alpha signaling is unknown. TNF-alpha signaling may involve sphingomyelin hydrolysis to ceramide by a sphingomyelinase and stimulation of a ceramide-activated protein kinase. In a cell-free system, TNF-alpha induced a rapid reduction in membrane sphingomyelin content and a quantitative elevation in ceramide concentrations. Ceramide-activated protein kinase activity also increased. Kinase activation was mimicked by addition of sphingomyelinase but not by phospholipas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
221
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(233 citation statements)
references
References 41 publications
11
221
0
1
Order By: Relevance
“…A number of extracellular stimuli, not only various cytokines including tumor necrosis factor (TNF)-a, interferon-g (Kim et al, 1991;Dressler et al, 1992), interleukin-1b (Ballou et al, 1992), nerve growth factor (Dobrowsky et al, 1994), and activators of Fas receptor (Cifone et al, 1994), but also physical stresses including heat shock, irradiation and chemotherapeutic drugs (Verheij et al, 1996;Santana et al, 1996;Ja rezou et al, 1996) are shown to cause sphingomyelin (SM) hydrolysis via sphingomyelinase (SMase), leading to elevation of intracellular ceramide, although several recent reports have questioned the role of ceramide in apoptosis induced by Fas or TNF-a (Sillence and Allen, 1997; Hsu et al, 1998;Watts et al, 1997Watts et al, , 1999a. The addition of exogenous ceramide has been associated with several antiproliferative responses including cell di erentiation, apoptosis, and cell cycle arrest (Okazaki et al, 1990;Kolesnick and Hannun, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A number of extracellular stimuli, not only various cytokines including tumor necrosis factor (TNF)-a, interferon-g (Kim et al, 1991;Dressler et al, 1992), interleukin-1b (Ballou et al, 1992), nerve growth factor (Dobrowsky et al, 1994), and activators of Fas receptor (Cifone et al, 1994), but also physical stresses including heat shock, irradiation and chemotherapeutic drugs (Verheij et al, 1996;Santana et al, 1996;Ja rezou et al, 1996) are shown to cause sphingomyelin (SM) hydrolysis via sphingomyelinase (SMase), leading to elevation of intracellular ceramide, although several recent reports have questioned the role of ceramide in apoptosis induced by Fas or TNF-a (Sillence and Allen, 1997; Hsu et al, 1998;Watts et al, 1997Watts et al, , 1999a. The addition of exogenous ceramide has been associated with several antiproliferative responses including cell di erentiation, apoptosis, and cell cycle arrest (Okazaki et al, 1990;Kolesnick and Hannun, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…4,46,47 Interestingly, the location of the sphingomyelin pool hydrolyzed by TNF-a is controversial. Several investigators have proposed that the TNF-asensitive pool resides in the external leaflet of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Since sphingolipids may be further metabolized into ceramide, a novel lipid mediator of apoptosis, in cultured cells, and since many apoptosis-inducing signals (including TNFα, chemotherapeutic drugs, Fas protein and ionizing radiation) have been demonstrated to activate apoptosis via ceramide formation [23,24], we investigated whether these sphingolipids might be converted into ceramide in order to elicit their cytocidal effects. We used the fungal agent fumonisin B1 (20 µM) to block the activity of ceramide synthase and therefore inhibit the conversion of sphingosine into ceramide, and we found that fumonisin B1 could not attenuate the apoptosis induced by sphingolipids (Table 3).…”
Section: Figure 1 Induction Of Apoptosis By Sphingosine In Hep3b Cellsmentioning
confidence: 99%